THE CONCEPT OF INDEPENDENT LEARNING IS VIEWED FROM THE PERSPECTIVE OF THOMAS LICKONA'S CHARACTER EDUCATION - Mochammad Rizky; Anita Puji Astutik (Nurul Jadid University, 2021)
This research wants to describe the perspective of character education from the thinking of Thomas Lickona which is linked to the free learning program pioneered by the Minister of Education and Culture of Indonesian (Kemendikbud) namely Nadiem Makarim, as a form of efforts to make the policy of independent learning plan has a concept in educating and improving the quality of personality of learners who are expected to have good traits, honest, devoted to parents, and responsible. The purpose of Thomas Lickona's education is to make the character of the child noble and smart using the method of shaping the child's personality in order to become a society, as well as a good citizen. This research has a qualitative approach and uses descriptive methods by collecting data and analyzing related programs of independent learning and character education of Thomas Lickona. The results of this study are expected to instil good habits so that students understand, can feel and want to do good.